An Empirical Analysis of Behaviour of Stock Market Indices: Evidences from Selected Developed and Developing Countries. Issue 2 (December 2016) - Bajaj, Sushil; Sethi, Naman
The present study aims to investigate the presence or absence of weak form market efficiency and unriddle the potential factors impacting the chaotic pattern of the stock market. The study carries the analysis by considering 12 countries' indices categorized as developing and developed on the basis of their GDP. Five econometric tools were applied for accomplishing the objectives and it was evidenced that the American and Indian stock market are weak-form inefficient whereas most of the statistical tools adjudged three countries (i.e., Hong Kong, Singapore & South Korea) weak-form efficient. It was also unveiled in the study that settlement cycle, information disclosure, thinness of trading, trading hours, and market size could be the potential reasons impacting the weak form of efficiency of the stock market.